Probiotic Ameliorate Gut Health and Growth Performance in Marwari Goat kids: A Substitute of Antibiotics - Pankaj Lavania; Kachhawaha, Subhash; Garbar Singh (Annals of Arid Zone, 2025)
Goat husbandry plays a vital role in providing house hold nutritional security, increased income and employment in rural transformation. In order to assess the influence of on-farm supplementary feeding of commercial probiotic on growth in growing kids has been evaluated. Twenty (3 months old) weaned kids of Marwari breeds were randomly divided into two groups of 10 each. One group served as control while the other as experimental group was fed probiotic @ 5 g kid-1d-1 for 90 days. Animals of both groups grazed on community pasture land. The results showed that probiotic supplemented experimental group gained significantly higher (P